Współczesne determinanty badań glottodydaktycz-nych. O perspektywach rozwoju glottogeragogiki - Jaroszewska, Anna (Neofilolog, 2019)
Modern social and cultural transformations from the second half of the 20th century and the beginning of the 21st century gave a strong impulse to fundamental reforms of European education systems. The same transfor-mations could not be unnoticed by the representatives of fields of knowl-edge for whom the present reality has become both a challenge and an op-portunity for development. These fields include language education and geragogics, being basically different but in some circumstances similar dis-ciplines. This view is more frequently confirmed by the involvement of these fields of study in the common area of research, namely foreign lan-guage learning and teaching of senior citizens. This area seems to be impor-tant in social terms and to have a great research potential. A proposal of cooperation between language education and geragogics under a new spe-cialised sub-discipline, i.e. senior language education is worth noting. This article is an attempt to determine arguments supporting the proposed the-sis. The course of discussion has been focused on the Polish background.